RETRACTED: Development issues of environmental culture in young people in globalization processes - Dilova Nargiza; Mardonova Soadat; Teshayev Azizbek; Halimovna Lobar (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001